1971
DOI: 10.1111/j.1365-2621.1971.tb06384.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Physical and Mechanical Treatments on the Tenderness of the Beef Longissimus

Abstract: 280 steaks from 56 beef carcasses were evaluated to determine the effects of different mechanical and physical methods for increasing the tenderness of the longissimus muscle. Changes in method of suspension, carcass integrity or chilling procedures resulted in increases in tenderness of approximately 47.5% for shear force and 53.6% for taste panel ratings. Experiment 2 (suspension from the achilles tendon, severonce between vertebrae in 5 locations, severance of the ligamentum nuchae and the attachment of 68 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

1973
1973
2015
2015

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(17 citation statements)
references
References 18 publications
(4 reference statements)
0
17
0
Order By: Relevance
“…(2) Smith et al (1978) reported that measures of tenderness of the broiled LD-rib are significantly (P < 0.01) related to the tenderness (shear force values and sensory panel tenderness ratings) of muscles from broiled or roasted cuts from every primal cut region (chuck, rib, loin, round) of the beef carcass. The harmonic mean correlation for LD-rib overall tenderness rating and shear force values for 14 muscles was -0.48.…”
Section: Use Of Longissimus Dorsi As An Indicator Musclementioning
confidence: 99%
“…(2) Smith et al (1978) reported that measures of tenderness of the broiled LD-rib are significantly (P < 0.01) related to the tenderness (shear force values and sensory panel tenderness ratings) of muscles from broiled or roasted cuts from every primal cut region (chuck, rib, loin, round) of the beef carcass. The harmonic mean correlation for LD-rib overall tenderness rating and shear force values for 14 muscles was -0.48.…”
Section: Use Of Longissimus Dorsi As An Indicator Musclementioning
confidence: 99%
“…Carcass side suspension effects on eating quality were described by Smith et al (1971), Hostetler et al (1970) and Bouton and Harris (1972). The factors which impact on the tenderstretch response were reviewed by Thompson et al (2006).…”
Section: Hanging and Agingmentioning
confidence: 97%
“…Cooling at +15"C (Croup I) enhanced the drip loss by 37%, indicating that conditions were produced during cooling which encouraged the development of watery tissue. The apparent advantage in tenderness obtained by holding excised muscles at 15.5"C, (Busch et al, 1967) or beef sides at + 15°C (Smith, Arango & Carpenter, 1971 ;Fields Smith st Carpenter, 1971;Busch et al, 1967) must therefore be equated with the commercial disadvantage of increased drip. I t is clear from Fig.…”
Section: IVmentioning
confidence: 96%